Development of the Magic Cube Numbers Educational Tool to Enhance Symbolic Thinking Skills in Children Aged 4-5 Years - Khodarsih, Delma; Sari, Meliana; Pérez, Carlos (Journal of Early Childhood Education and Teaching (JECET), 2025)
Purpose – Symbolic thinking is a fundamental cognitive ability that enables children to understand and use symbols, such as numbers and letters, to represent real-world concepts. This study aims to develop the Magic Cube Numbers educational tool to enhance symbolic thinking skills in children aged 4–5 years. Design/methods/approach – This research utilizes a Research and Development (R&D) approach, adopting the 4D model by Thiagarajan—Define, Design, Develop, and Disseminate—while focusing on the Develop stage. Data were collected using expert validation sheets and teacher practicality questionnaires, with evaluations conducted by two expert validators and two practitioner teachers. Findings – The Magic Cube Numbers tool obtained a validity score of 82.14%, categorized as "very valid," and a practicality score of 93.84%, categorized as "very practical." These results demonstrate the tool’s relevance, usability, and potential to support children’s symbolic thinking development. Research implications/limitations – The findings suggest that Magic Cube Numbers is an effective medium for strengthening symbolic recognition and early numeracy. However, the study is limited by its small sample size and specific setting. Broader testing and long-term observation are recommended for generalization and sustainability. Originality/value – This study offers a novel contribution by focusing specifically on symbolic thinking—an often underrepresented aspect of early cognitive development. Through a play-based approach that integrates numerical and alphabetical symbols, Magic Cube Numbers provides practical value for educators and enriches early learning strategies rooted in cognitive development theory.